Promoting Sports Engagement during the COVID-19 Pandemic via Virtual Reality Games. (25th January 2022) - Hanifah, Hana; Ito, Yuko; Yao, Daryl Patrick Gamboa; Suyama, Natsuka; Inoue, Kaoru
Abstract : Rationale . Sedentary activities are perpetuated by aging and the COVID-19 pandemic. While demands for video games grow, few studies explored the potential of virtual reality (VR) games to promote sports engagement and health among young adults. Objective . To examine sports engagement and health changes of young adults when utilizing a VR sports game and investigate the relationship between sports engagement and health. Method . This study used a single-group design with 20 participants, aged 19–29 years, with no preexisting health conditions. The VR game "Sports Scramble" was used thrice within a span of one week. Outcomes sought include sports engagement and health, measured through the Sports Engagement Scale (SES) and Short Form 36 (SF-36), respectively. Results . A significant difference (p < 0.001 ) was found between the pre-posttest scores of the SES. Moreover, a positive trend was observed in terms of health with a significant difference (p < 0.05 ) between pre-posttest scores of the SF-36's vitality dimension. There were positive correlations among the dedication and vigor subscales of the SES with the dimensions of health. Conclusion . This study showed the potential of VR sports games in positively influencing sports engagement and health among participants with the vigor and dedication positively influencing health. Future studies may involve the exploration of the effectiveness of VR to promote engagement and health through a randomized controlled trial with a longer timeframe and across various populations.